Development of the Method for Calculation of Reinforced Concrete Structures on the Formation and Opening of Normal Cracks - Nikolay N. Trekin; Emil N. Kodysh; Sergey G. Parfenov; Konstantin R. Andrian (Железобетонные конструкции)
This paper presents the history of the development of the method for calculating the crack resistance of reinforced concrete elements according to Soviet and modern design standards, which was based on the work of the Soviet and foreign scientists, such as: A.F. Loleit, V.I. Murashev, A.A. Gvozdev, S.A. Dmitriev, A. Clark, J. Monier and others. Also, the article discusses the currently updated calculation methods for the formation and opening of normal cracks according to domestic and foreign standards.